Reducing radiotherapy target volume expansion for patients with HPV-associated oropharyngeal cancer. (May 2019) - Burr, Adam R.; Harari, Paul M.; Ko, Huaising C.; Bruce, Justine Y.; Kimple, Randall J.; Witek, Matthew E.
Highlights: Excellent locoregional control of HPV + OPSCC is achieved with direct GTV to PTV expansions. The majority of treatment failures were located within the high-dose planning volume. Low toxicity profile was achieved with one-year gastrostomy tube retention rate of 6%. Abstract: Purpose: To evaluate clinical outcomes and patterns of failure using a direct gross tumor volume to planning target volume expansion in patients with p16-positive oropharyngeal squamous cell carcinoma. Methods and materials: We performed a retrospective review of patients with p16-positive oropharyngeal squamous cell carcinomas treated between 2002 and 2017 with primary radiotherapy with or without concurrent systemic therapy. Patient and disease characteristics associated with disease control and clinical outcomes were analyzed by Cox proportional hazards regression and Kaplan-Meier analyses. Imaging at the time of first failure was used to categorize failure patterns. Results: We identified 134 patients with a median follow-up of 56.2 months (range 8.2–160.2 months). Local and regional control at 5 years was 91.5% (95% CI: 86.8–96.4%), and 90.8% (95% CI: 85.6–96.2%), respectively. Of the 14 locoregional failures, there were 10 in-field (Type A), 3 marginal (Type B), and 1 geographic (Type E). Age >70 years (HR 5.42; 95% CI: 1.87–15.68) and T4 versus T1-3 (HR 4.09; 95% CI: 1.01–2.65) were associated with increased rates of locoregional failure on multivariate analysis. The rate of gastrostomy tube retention at one year was 6.0% (range 2.8–12.7%). Conclusions: Management of patients with p16-positive oropharyngeal squamous cell carcinoma using definitive radiotherapy and a high-dose planning target volume created without a gross tumor volume to clinical tumor volume expansion resulted in high locoregional control with the vast majority of failures occurring within the high-dose field. These data warrant prospective evaluation of this technique as a therapy de-intensification approach.